HSE training matrices templates for grassroots posts in petroleum and petrochemical enterprises - Shao-Lin Qiu (KeAi Communications Co., Ltd., 2017)
Abstract This paper aims to standardize health, safety and environment (HSE) training matrices for effectively identifying training requirements and enhancing job competency of grassroots posts in petroleum and petrochemical enterprises. After an investigation into HSE training performance in petroleum and petrochemical enterprises, HSE training matrices templates for 239 grassroots posts involving 22 primary petroleum and petrochemical disciplines were developed based on the technical requirements of HSE training matrices templates and the studies of template development processes and technical methods at grassroots level. Applications of these templates in 12 companies demonstrate their effectiveness in improving HSE training and management for grassroots posts, strengthening risk control and promoting the application of HSE system and tools in grassroots units.